Global Monitoring of Geomagnetic Storm‐Induced Ionosphere Anomalies Using 3‐D Ionospheric Modeling With Multi‐GNSS and COSMIC Measurements. Issue 2 (19th February 2021) - Cheng, Na; Song, Shuli; Jiao, Guoqiang; Jin, Xulei; Li, Wei
Abstract: Ionosphere is a signiﬁcant component of the solar‐terrestrial space environment. Geomagnetic storm induces global ionospheric disturbances, severely affect radio communications and human space activities, e.g., earth observation, deep space exploration, and space weather monitoring and prediction. Monitoring ionospheric anomalies are critical to improve the performance of Global Navigation Satellite System (GNSS) positioning, navigation and timing (PNT) and provide early‐warning of disaster service during the extreme space weather event. The spatial and temporal variation of ionospheric electron density (IED) is utilized to characterize the ionospheric anomalies respond to storm. Thus, the global‐scale three‐dimensional (3‐D) ionospheric model is constructed by computerized ionospheric omography (CIT) technique combine multi‐GNSS(GPS/GLONASS/BDS/Galileo) and Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) radio occultation (RO) measurements. As ground‐based multi‐GNSS and space‐based Low Earth Orbit (LEO)/GNSS observation networks expand gradually, massive measurements are employed in ionospheric inversion in high temporal‐spatial resolution. Hence, the Open Multi‐Processing (OpenMP) parallel computing method is applied to improve the efﬁciency of imaging 3‐D ionosphere. The processing time reduces to within 10 mins, thus 3‐D ionospheric model updates in near real‐time is achievable. Moreover, the 3‐D IED model is applied to monitor the ionosphere dynamically during storms and the storm‐induced ionospheric anomalies are observed. This contribution suggests our reconstructed 3‐D model is capable of reﬂecting the ionospheric anomalies during storm in global‐scale, also it reveals the characteristics of the ionosphere respond to the storm and its evolution. Key Points: Multi‐GNSS (GPS/GLONASS/BDS/Galileo) multifrequency observations are first utilized to the 3‐D ionosphere modeling. Near real‐time global‐scale 3‐D is constructed by adopting OpenMP parallel processing and the IED product is achievable on our platform. Monitor the storm‐induced ionospheric anomalies in global scale and reveal the spatial and temporal characteristics of the ionosphere.